Place product in the promotion of communes – the case of the Milicz carp and the Barycz Valley - Glinka, Kamil (Journal of Education Culture and Society, 2020)
The constant competitiveness for the interest of entrepreneurs, tourists, students makes that local government units put effort into creating their image. However, the limited capital and organizational resources make that these units initiate multilateral promotion actions. Preparing its offer they repeatedly use attractive place products.The main aim of the article is to answer the question whether, if so in what ways, the Milicz carp, treated as a place product, is used in the promotion of the Local Action Group “Partnership for the Barycz Valley” created by the eight communes of Lower Silesia and Wielkopolskie province. Especially while taking into account two elements: first, the premises of the official strategic documents adopted within ‘the Barycz Valley’, second, the conducted in practice promotion actions. The use of two methods: content analysis and comparative analysis allows to state that the Milicz carp, against the goals in the given documents, plays a significant role in the promotion of the cooperating communes. Actions in the field of public relations have the greatest importance. On the other hand, the actions concerning the promotion of the Milicz carp do not accompany all the enterprises shaping the image of ‘the Barycz Valley’.